Structure-wave absorption integrated in-situ growth foam filled honeycomb material and preparation method and application thereof

By growing and filling hard functional composite foam materials in situ in honeycomb materials, supercritical foaming technology is used to enhance the compressive and wave absorption performance of the material, the problem of insufficient compressive performance of honeycomb materials in the plane direction is solved, and the dual function improvement of the material is achieved.

CN119898041AActive Publication Date: 2025-04-29SOUTHWEST JIAOTONG UNIV
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510222111.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-29
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The existing honeycomb materials have weak compressive resistance in the plane direction and are prone to collapse when under pressure. They are prone to problems such as grid wall collapse and layered tearing during processing, making it difficult to meet the needs of use in harsh environments.

Method used

By growing the filled hard functional composite foam material in situ in the honeycomb material, the foam is filled inside the honeycomb hole using supercritical foaming technology to enhance the overall stiffness and strength of the material and improve its absorbing performance.

Benefits of technology

It realizes isotropic enhancement of honeycomb materials, improves the compressive and wave absorbing properties of the materials, especially the maximum compression stress in the plane direction is significantly improved, and is suitable for use in aerospace, military protection and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898041A_ABST
    Figure CN119898041A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of advanced composite materials, and particularly relates to a structure-wave absorption integrated in-situ growth foam filled honeycomb material and a preparation method and application thereof. The preparation method comprises the following steps: putting a polyvinylidene fluoride composite material into a mold, covering polyvinylidene fluoride granules with a high-temperature-resistant film, carrying out hot pressing, placing, pressing, and cooling to obtain a polyvinylidene fluoride plate; putting the plate into a mold, putting the honeycomb on the plate, standing and melting, and pressing the honeycomb into the plate to obtain a honeycomb composite material; the honeycomb composite material is placed in a fixed-size mold in a supercritical foaming kettle, then carbon dioxide fluid is injected, pressure and temperature are controlled, after heat and pressure preservation, pressure relief and cooling shaping are conducted, and the foam-filled honeycomb material is obtained. The foam-filled honeycomb material obtained by the preparation method realizes in-situ growth, a honeycomb is filled with full foam, and the foam is uniform and fine in morphology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of advanced composite materials, and in particular relates to an in-situ grown foam-filled honeycomb material with integrated structure and wave absorption, and a preparation method and application thereof. Background Art

[0002] Advanced composite materials are a type of composite materials with excellent performance and broad application prospects. By combining two or more different materials, the advantages of each material are fully utilized to create new materials with specific and advanced functions.

[0003] Honeycomb material is a composite material, which is usually called honeycomb structure in the aerospace field. Honeycomb structure is a sandwich structure, whose core layer is composed of a series of hexagonal, quadrilateral or other shaped honeycomb-like cells, and thinner panels / skins are glued (or brazed) on the upper and lower sides of the sandwich layer. Honeycomb structure has higher strength and stiffness than other forms of sandwich structure. In the aerospace industry, honeycomb sandwich structure is often used to make various wall panels, wing surfaces, decks, hatches, floors, engine guards, tail nozzles, silencers, heat insulation panels, satellite shells, etc. In addition, honeycomb absorbing materials, as a lightweight functional material with excellent electromagnetic wave absorption performance, have been used in aircraft structural stealth components, such as wing leading edges, doors and radomes for radar stealth, effectively reducing the aircraft's radar reflection cross section while maintaining structural strength and lightweight characteristics.

[0004] However, although honeycomb materials have good pressure resistance in the thickness direction, their performance in the plane direction is relatively weak in terms of pressure resistance, which makes it difficult to meet the requirements of use in harsh environments. Especially when under pressure, the honeycomb structure is easily crushed, resulting in structural failure. At the same time, when cutting aramid paper honeycombs, due to weak rigid support and significant fiber anisotropy, honeycomb cell wall collapse and deformation, delamination and tearing are very likely to occur, resulting in low processing efficiency and difficult to control processing quality.

[0005] Therefore, how to improve the compression strength of honeycomb materials and improve their processing performance has become an urgent problem to be solved. The existing methods for enhancing the mechanical strength of honeycombs are mainly through: impregnation reinforcement and honeycomb paper pressed into hard foam reinforcement; for the impregnation reinforcement method, the resin impregnation reinforcement method widely used in the prior art can partially improve the mechanical properties, but the limitation is that it requires a multi-stage impregnation-curing cycle, resulting in high energy consumption and long cycle, and the excessive penetration of the resin will cause pore blockage, seriously affecting the material's air permeability, electromagnetic wave transmission and other additional functions;

[0006] For the method of pressing honeycomb paper into rigid foam for reinforcement, which is aimed at rigid foam with high mechanical strength, the honeycomb is prone to curling and deformation during the pressing process, resulting in a decrease in the reinforcement effect or even structural failure. Therefore, the development of a honeycomb material modification technology that can achieve isotropic reinforcement and maintain processing adaptability has become an urgent need for lightweight design in the fields of aviation, rail transit, etc.

[0007] In addition, in terms of wave absorption performance, the performance improvement of impregnated wave absorbing honeycomb materials has reached a bottleneck. Especially under the strict requirements of lightweight in the aviation field, the method of enhancing the wave absorption performance by simply increasing the thickness of the absorbent wall is insufficient. This method not only improves the overall quality of the honeycomb, but also because the effective thickness of the radar wave and the honeycomb is thin, most of the space is still filled with air without wave absorption function, which limits the full interaction between radar waves and materials. Therefore, there is an urgent need for a structure-wave absorption integrated in-situ growth foam filled honeycomb material and its preparation method to solve the problems and limitations of the existing technology. Summary of the invention

[0008] In view of the problems existing in the prior art, the present invention provides a method for preparing an in-situ grown foam-filled honeycomb material with integrated structure and wave absorption, comprising the following steps:

[0009] S1: placing a polyvinylidene fluoride composite material in a mold, covering the polyvinylidene fluoride pellets with a high temperature resistant film, performing hot pressing, placing and pressing, and obtaining a polyvinylidene fluoride sheet after cooling;

[0010] S2: putting the plate obtained in S1 into a mold, placing the honeycomb on the plate, allowing it to stand at high temperature and melt, and then pressing the honeycomb into the plate to obtain a honeycomb composite material;

[0011] S3: placing the honeycomb composite material obtained in S2 into a fixed-size mold in a supercritical foaming reactor, and then injecting carbon dioxide fluid, controlling the pressure and temperature, and after heat and pressure maintenance, releasing the pressure, cooling and shaping to obtain a foam-filled honeycomb material.

[0012] Furthermore, the temperature during the hot pressing process described in S1 is 200°C.

[0013] Furthermore, the inner cavity size of the fixed-size mold described in S3 is 250 mm×250 mm×200 mm.

[0014] Furthermore, the size of the honeycomb described in S2 is consistent with that of the plate.

[0015] Furthermore, the pressure in S3 is 13-20 MPa, the temperature is 120-140° C., and the time of heat preservation and pressure preservation is 0.5-2 h.

[0016] A structure-wave absorption integrated in-situ growth foam filled honeycomb material, the structure-wave absorption integrated in-situ growth foam filled honeycomb material is a filled honeycomb structure with full foam, the pore structure of the foam is 30-50 microns, and the foam morphology is uniform and fine.

[0017] The invention discloses an application of a structure-wave absorbing integrated in-situ grown foam-filled honeycomb material, wherein the structure-wave absorbing integrated in-situ grown foam-filled honeycomb material is applied in the preparation of aircraft structural stealth components.

[0018] Beneficial Effects

[0019] The present invention presses the honeycomb into a polyvinylidene fluoride composite material, fills the honeycomb material in an in-situ growth manner, and fills the hard functional composite foam material inside the honeycomb hole through advanced supercritical foaming molding technology, thereby achieving a dual improvement in the structure and function of the honeycomb material while ensuring the lightweight characteristics. The in-situ filling foam supports the honeycomb wall, reduces local buckling while maintaining the lightweight characteristics, improves the overall stiffness and strength of the material, and the maximum compressive stress in the thickness direction can be increased by 310% (from 0.1MPa to 0.31MPa). At the same time, in the plane direction (W and L), the maximum compressive stress can be increased from 0.3KPa to 65Kpa. The energy absorption characteristics of the foam significantly improve the impact absorption capacity of the filled honeycomb structure in all directions, which is particularly suitable for protective structures. The sealed foam structure effectively isolates heat and sound transmission, and is suitable for buildings and vehicle noise reduction applications that require good insulation performance. These technical advantages make foam-filled honeycomb materials have broad application prospects in aerospace, military protection, transportation, construction and automotive industries.

[0020] The present invention uses absorbing foam to fill the honeycomb hole structure, which can transform the interaction between radar waves and honeycombs from surface interaction to volume interaction, which not only provides more absorbing space, but also achieves ultra-high foaming rate through supercritical foaming technology, greatly reducing the density of the foam. This method effectively converts surface absorption to volume absorption while maintaining the lightweight characteristics of the material, significantly improving the absorption performance of radar waves. The in-situ filling foam technology also enhances the processability of honeycomb materials, can meet more complex structural design requirements, and reduce production and design costs. In addition to carbon nanotubes, the absorbing filler in the present invention can also use graphene and carbonyl iron; the preparation method in the present invention is also applicable to other thermoplastic polymers (PP, PS, PA, PC, PMMA, TPU); the foaming agent involved in the present invention can also be nitrogen, ethanol, butane. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0022] Figure 1 The schematic diagram and scanning electron microscope image of the in-situ growth foam of the aramid paper honeycomb obtained in Example 1 of the present invention;

[0023] Figure 2 This is a scanning electron microscope image of a schematic diagram of the in-situ growth of the aramid paper honeycomb absorbing foam obtained in Example 1 of the present invention;

[0024] Figure 3 This is a test diagram of the pressure resistance of the foam-filled honeycomb material obtained in Example 1 of the present invention;

[0025] Figure 4 This is a diagram showing the wave absorbing performance of the wave absorbing foam filled honeycomb material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments 1 to 2 of the present invention and the attached Figures 1 to 4 , the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present invention provides a method for preparing a structure-wave absorbing integrated in-situ grown foam-filled honeycomb material, comprising:

[0028] S1: Weigh the foaming raw material polyvinylidene fluoride composite material, put it in a mold, cover the polyvinylidene fluoride pellets with a high temperature resistant film (PI), and put it into a hot press; adjust the parameters of the hot press, and then leave it for a suitable time to ensure that the PVDF is melted, and then press and cool to obtain a polyvinylidene fluoride sheet.

[0029] S2: putting the polyvinylidene fluoride sheet obtained in S1 into a mold, placing honeycomb paper of the same size as the polyvinylidene fluoride sheet on the sheet, and performing hot pressing to ensure that the sheet is melted, and then repeatedly pressing the honeycomb material into the sheet with low pressure, and after cooling, obtaining a honeycomb composite material;

[0030] S3: The honeycomb composite material obtained in S2 is placed in a constrained mold in a supercritical foaming reactor, and then carbon dioxide fluid is injected, and the parameters are controlled. After heat preservation and pressure maintenance, the pressure relief valve is turned on to release the pressure to normal pressure, and finally the sample is cooled and shaped with an ice-water mixture to obtain an in-situ grown foam-filled honeycomb material.

[0031] Example 1

[0032] S1: 8g of polyvinylidene fluoride pellets are selected and placed in a mold, and the surface is covered with a high temperature resistant PI film to ensure that the surface is regular; then it is placed in a hot press, and allowed to stand at 200°C for 10 minutes to ensure that it is melted, and a pressure of 5MPa is used and vacuum is applied, and after cooling, a 2mm thick polyvinylidene fluoride sheet is obtained;

[0033] S2: Using the same mold as S1, the honeycomb was placed on the plate, and after standing at 200°C for 10 minutes to melt, the honeycomb was slowly pressed into the plate multiple times with a pressure of 0.5 MPa to obtain a honeycomb composite material; the honeycomb thickness was 15 mm;

[0034] S3: Place the honeycomb composite material into a square stainless steel mold with an inner cavity size of 250mm×250mm×200mm, ensure that the stainless steel mold is placed flat, and put the cut honeycomb composite material in; inject carbon dioxide fluid, control the pressure to 16MPa, and the temperature to 126℃, keep the temperature and pressure for 0.5h, then unscrew the pressure relief valve to release the pressure to normal pressure, and finally use an ice-water mixture to cool and shape the sample to obtain a foam-filled honeycomb material with an expansion ratio of 8 times.

[0035] Example 2

[0036] 50 g of polyvinylidene fluoride pellets were selected and put into the feed barrel of a twin-screw extruder, and 2.5 g of carbon nanotube powder was added in batches; the temperature of the extruder feed section was set to 200° C., and the temperature of the melting section and the extrusion section was set to 220° C., and the pelletization was performed multiple times to ensure uniform mixing. After pelletizing, polyvinylidene fluoride composite material pellets containing 5% carbon nanotubes were obtained, which were collected for subsequent use;

[0037] S1: 8g of the above composite material pellets are selected and placed in a mold, and the surface is covered with a high temperature resistant PI film to ensure that the surface is regular; then it is placed in a hot press, and is allowed to stand at 200°C for 10 minutes to ensure that it is melted, and a pressure of 5MPa is used and vacuum is drawn, and after cooling, a 2mm thick polyvinylidene fluoride (5% carbon nanotube) composite sheet is obtained;

[0038] S2: Using the same mold as S1, the honeycomb was placed on the plate, and after standing at 200°C for 10 minutes to melt, the honeycomb was slowly pressed into the plate several times using 0.5MPa to obtain a honeycomb composite material; the honeycomb thickness was 15mm;

[0039] S3: Place the honeycomb composite material into a square stainless steel mold with an inner cavity size of 250mm×250mm×200mm, ensure that the stainless steel mold is placed flat, and put the cut honeycomb composite material in; inject carbon dioxide fluid, control the pressure to 16MPa, and the temperature to 127℃, keep the temperature and pressure for 0.5h, then unscrew the pressure relief valve to release the pressure to normal pressure, and finally use an ice-water mixture to cool and shape the sample to obtain a foam-filled honeycomb material with an expansion ratio of 8 times.

[0040] Combination Figure 1 A schematic diagram of the in-situ growth of aramid paper honeycomb foam and its scanning electron microscope image can be obtained. The present invention achieves complete filling of fine foam in the inner cavity of the aramid paper honeycomb through the in-situ foaming molding process. The interface between the foam and the honeycomb wall is dense and defect-free. The SEM image shows that the filled foam has a closed-cell structure, and the pore size is evenly distributed in the range of 20-40μm. The high proportion of micron-level closed cells provides stable mechanical support and multiple scattering paths for electromagnetic waves for the material. And after the introduction of absorbing fillers ( Figure 2 ) can still maintain uniform filling characteristics.

[0041] from Figure 3 It can be known that the pressure resistance of foam-filled honeycomb materials, Figure 3 (a) is the pressure diagram in the thickness direction. Foam filling increases the maximum compressive stress in the thickness direction of the honeycomb material by 310% (from 0.1MPa to 0.31MPa). Figure 3 (b) is the pressure diagram in the W and L directions. It can be seen from the figure that the filling of foam greatly enhances the pressure resistance of the honeycomb structure in the plane direction, and the maximum compressive stress increases by 2166% (0.3kPa→65kPa). Figure 4 It can be seen from the absorbing performance of the absorbing foam filled honeycomb material (5% wt CNT) that full absorption of the X-band (8-12 GHz) is achieved at a thickness of 4 mm, with a maximum reflection loss of -28 dB.

[0042] Through the preparation method of a structure-wave absorption integrated in-situ growth foam-filled honeycomb material provided by the present invention, the aramid paper honeycomb is in-situ grown and filled to enhance. The prior art uses embedding means, but it will destroy the structure of the honeycomb and the foam, so it cannot be mass-produced and applied; and the foam pores prepared by the preparation method of the present invention are uniform, and the pore size is less than 50μm, which cannot be achieved by similar honeycomb foam products in the prior art; and the process of the present preparation method is simple and environmentally friendly, and the mechanical properties of the honeycomb are greatly improved, especially the compression resistance in the plane direction. And the preparation method of the present invention can introduce electromagnetic functional materials into the foam component to realize the structural and functional integration of the honeycomb foam. The preparation method adopted in the prior art does not have the ability to evenly disperse the conductive filler and cannot achieve a good wave absorption effect. The synergy of the honeycomb and the wave-absorbing foam in the preparation method of the present invention applies the supercritical fluid foaming technology to the high-performance structural honeycomb, which has never been mentioned in the prior art.

Claims

1. A method for preparing an in-situ grown foam-filled honeycomb material with integrated structure and wave absorption, characterized in that: The following steps are involved: S1: placing a polyvinylidene fluoride composite material in a mold, covering the polyvinylidene fluoride pellets with a high temperature resistant film, performing hot pressing, placing and pressing, and obtaining a polyvinylidene fluoride sheet after cooling; S2: putting the plate obtained in S1 into a mold, placing a honeycomb on the plate, allowing it to stand and melt, and then pressing the honeycomb into the plate to obtain a honeycomb composite material; S3: placing the honeycomb composite material obtained in S2 into a fixed-size mold in a supercritical foaming reactor, and then injecting carbon dioxide fluid, controlling the pressure and temperature, and after heat and pressure maintenance, releasing the pressure, cooling and shaping to obtain a foam-filled honeycomb material.

2. The method for preparing a structure-wave absorbing integrated in-situ grown foam-filled honeycomb material according to claim 1, characterized in that: The temperature during the hot pressing process described in S1 was 200°C.

3. The method for preparing a structure-wave absorbing integrated in-situ grown foam-filled honeycomb material according to claim 1, characterized in that: The inner cavity size of the fixed-size mold described in S3 is 250 mm×250 mm×200 mm.

4. The method for preparing a structure-wave absorbing integrated in-situ grown foam-filled honeycomb material according to claim 1, characterized in that: The dimensions of the honeycomb described in S2 are consistent with those of the plate.

5. The method for preparing a structure-wave absorbing integrated in-situ grown foam-filled honeycomb material according to claim 1, characterized in that: The pressure described in S3 is 13-20 MPa, the temperature is 120-140° C., and the time of heat preservation and pressure preservation is 0.5-2 h.

6. An in-situ grown foam filled honeycomb material with integrated structure and wave absorption obtained by the preparation method according to any one of claims 1 to 5, characterized in that: The structure-wave absorbing integrated in-situ grown foam filled honeycomb material is a filled honeycomb structure with full foam, the pore structure of the foam is 30 to 50 microns, and the foam morphology is uniform and delicate.

7. The use of an in-situ grown foam filled honeycomb material with integrated structure and wave absorption according to claim 6, characterized in that: The structure-wave absorbing integrated in-situ grown foam-filled honeycomb material is used in the preparation of aircraft structural stealth components.

Citation Information

Patent Citations

  • Method for manufacturing honeycomb composite foam structure sandwiched veneer plate for buildings

    CN102514349A

  • Paper honeycomb sandwich structure composite board and preparation method thereof

    CN105365325A

  • Cellular sandwich structure and production method thereof

    CN106003850A

  • Fluorine-containing polymer flat sheet membrane and method for preparing same

    CN109078500A

  • Composite foam material with three-layer gradient foam structure as well as preparation method and application of composite foam material

    CN118181801A